The Development of Speaking Skills using the Immersion Teaching Model: A Case Study of a 5th Grade Greek Primary Class in an EFL Context - Nteli, Athina; Zafiri, Makrina (Open Science Journal, 2017)
This paper investigates the development of students’ speaking skills, using the Immersion Teaching Model (ITM) as a form of process differentiation. It aims to explore whether the ITM intervention in an English as a Foreign Language (EFL) context will have an impact on the students’ speech development and motivation, and will furthermore investigate its feasibility as a teaching approach. A 5th Grade class of a Greek state Primary school was used and action research was implemented. The research findings revealed enhancement of the speaking skills for the students that have at least an initial level of language speaking competence, but no difference was detected for the students of no speaking competence, indicating the need for further differentiation. However, the ITM intervention was proven feasible to use in the EFL classroom and highly affective to student motivation. The implications of the present research for the EFL context have shown that the ITM is flexible enough to accommodate the diverse educational needs, and benefit meaningful speech production if appropriately applied.